Evaluation of Health and Safety Status of Public and Private Building Construction Projects in Pokhara - Adhikari, Sujan; Giri, Om Prakash (Himalayan Journal of Applied Science and Engineering, 2024)
Health and safety (H&S) in the construction industry encompasses a set of principles, regulations, practices, and measures designed to safeguard the well-being and safety of construction teams within construction environments. Developing countries like Nepal lag in establishing and implementing robust H&S regulations, impacting overall project performance. This research assesses the H&S status in public and private building construction projects within Pokhara Valley, Nepal. One private and one public project were selected for the investigation. After conducting a thorough literature review and consulting key informants, a structured five-point Likert scale questionnaire was developed for efficient data collection. Findings revealed that H&S aspects in privately and publicly owned building construction projects. Privately owned projects underscored effective ventilation, hard hats, and daily safety briefings are significant factors. Slip, trip, and fall incidents are major accident causes, highlighting the importance of proper lighting. Public projects emphasized ventilation, hard hats, and safety rules, with toolbox talks and qualified team members deemed critical. Slip, trip, and fall incidents remained the primary accidents, and safety signs played a pivotal role. These findings offer essential guidance for policymakers and construction managers to enhance H&S practices in diverse construction environments.